Adapting forest certification to climate change. (12th November 2014) - Klenk, Nicole L.; Larson, Brendon M. H.; McDermott, Constance L.
Abstract : In the context of climate change, the forest sector must consider the extent to which sustainable forest management enables or constrains climate change adaptation and mitigation; it may be that existing values and principles, policies and decision‐making processes, and institutions are no longer appropriate. Forest certification has emerged as an important arena for setting international and regional standards for forest management, but it is unclear to what extent it supports or helps develop adaptive capacity for climate change in the forest sector. This paper, therefore, combines a review of the literature on forests and climate adaptation with a systematic assessment of the Forest Stewardship Council Criteria and Indicators (in detail) and other forest and carbon certification schemes (in brief) to shed light on the role of certification standards in mediating forest and climate adaptation strategies. WIREs Clim Change 2015, 6:189–201. doi: 10.1002/wcc.329 This article is categorized under: Climate, Ecology, and Conservation > Conservation Strategies Vulnerability and Adaptation to Climate Change > Institutions for Adaptation Policy and Governance > Multilevel and Transnational Climate Change Governance